Factors associated with motor complications in Parkinson's disease. Issue 10 (25th September 2017) - Kadastik‐Eerme, Liis; Taba, Nele; Asser, Toomas; Taba, Pille
Abstract: Objectives: Levodopa is the most effective therapy for treating Parkinson's disease (PD); however, side effects such as dyskinesias and motor fluctuations may occur after some years of its usage. The aims of this study were to assess the frequency of and factors associated with motor complications among PD patients on levodopa treatment. Methods: In a cross‐sectional study carried out in 2010–2013, clinical data and treatment details were collected. Logistic regression expressed by odd ratios (OR) and 95% confidence intervals (CI) was conducted to examine the effects of several independent variables on the occurrence of motor complications. Results: A total of 455 patients were enrolled, among whom 374 were on levodopa. Analysis was performed in 328 patients whose exact duration of levodopa treatment was known. Among patients included in the analysis, 25.9% experienced motor complications; of these, 21% had dyskinesias and 20.1% had motor fluctuations. Based on logistic regression, statistically significant factors associated with the occurrence of motor complications were younger age at onset of the disease, higher levodopa equivalent daily dose (LEDD), shorter time to levodopa initiation, and akinetic‐rigid dominant phenotype of PD. Conclusions: This study suggests that postponing the start of levodopa therapy and maintaining low daily doses of levodopa might reduce the risk of motor complications. Our results confirm that due to higher risk of motor complications, effectively treating patients with akinetic‐rigid dominant phenotype of PD might be more challenging than for patients whose dominant symptom is tremor. Abstract : This article describes motor complications in patients with Parkinson's disease (PD) on levodopa treatment, and assesses the effect of various demographic and clinical factors on their occurrence. Our findings revealed that postponing the start of levodopa therapy and maintaining lower daily doses might reduce the risk of motor complications. Also, the clinical subtype of PD is of importance: due to higher risk for motor complications in patients with akinetic‐rigid subtype, finding the optimal treatment strategies for them might be more challenging than for patients with tremor‐dominant subtype of PD.